Nowe życie, czyli Polak potrafi(ł) - Jakubowski, Piotr (Załącznik Kulturoznawczy, 2019)
The article is a discussion with Dionisios Sturis’ reportage book Nowe życie. Jak Polacy pomagali uchodźcom z Grecji (New Life. How Poles Were Helping the Greek Refugees), especially with the parts where Sturis draws a historical parallel between actions of Polish People Republic’s authorities from late 40s and early 50s – who decided to harbour the children, civilians and wounded partisans from Greek home war – and current ones, who refuse to accept the nowadays refugees from Africa and Middle East. While the author is aloof to the rhetoric which presents the former ones as a guiding light to the latter – as Sturis used to do – he still claims that the book could serve as a tool of empowering anti-xenophobic and inclusive ‘policy of hope’ (according to Rebecca Solnit’s notion).